Necesidad de formación de posgrado en el campo de la enfermería. Zona 3. Marzo-julio 2022 - Guamán Curi, Célida Grey (2022)
The present research entitled "NEED FOR POSTGRADUATE TRAINING IN THE FIELD OF NURSING. ZONE 3. MARCH-JULY 2022" had as its objective "To determine the need for postgraduate training in the field of nursing in Zone 3 of Ecuador, during the period March-July 2022". Following the methodology of xvi quantitative approach, descriptive, cross-sectional, descriptive design. The sample consisted of 219 nursing professionals from Zone 3 and 50 employers, who voluntarily responded to a survey sent via the Internet using the Google Form platform, whose responses generated tables whose analysis showed that 100% of the nursing professionals indicate that they need to have postgraduate studies to improve in the labor field and provide better care, while employers consider 100% that there is a need for nursing professionals with postgraduate studies in Zone 3. The conclusion is that the nursing professionals in Zone 3 wish to continue their studies in order to improve their care and humanized care skills, improve their knowledge and skills in the labor field, improve their communication skills and, to a lesser extent, to improve their leadership skills.